Growth promotion of Bifidobacterium and Lactobacillus species by proteinaceous hydrolysates derived from poultry processing leftovers. (24th October 2012) - Lazzi, Camilla; Meli, Federica; Lambertini, Francesca; Bottesini, Chiara; Nikolaev, Ilya; Gatti, Monica; Sforza, Stefano; Koroleva, Olga; Popov, Vladimir; Neviani, Erasmo; Dossena, Arnaldo
Summary: Bacterial growth media represent a high cost in industrial applications, and for this reason, it is economically important to find less expensive supplements to replace the traditional ones. In the present work, peptide hydrolysates obtained from poultry meat and bone residues (functional animal protein [FAP]) and from feathers (functional feather protein [FFP]) were studied to determine their ability for the production of microbial biomass with improved viability. The results obtained were compared with those obtained with other supplement nutritive compounds used in fermentation growth media. The molecular composition of the hydrolysates in terms of total and soluble nitrogen, molecular weight distribution, total and free amino acids, was determined. The growth and cellular state of Bifidobacterium and Lactobacillus strains were studied by turbidimetric measurements and direct count by fluorescence microscopy. Overall, this study suggested that by‐products from poultry industry provide a good alternative to substitute expensive supplements for growth of Lactobacillus and Bifidobacterium with a high level of viability.